2013
DOI: 10.1007/s12088-013-0381-4
|View full text |Cite
|
Sign up to set email alerts
|

Production of N-acyl Homoserine Lactones and Virulence Factors of Waterborne Aeromonas hydrophila

Abstract: Aeromonads are inhabitants of aquatic ecosystems and are described as being involved in intestinal disturbances and other infections. The purpose of this study was to investigate the production of N-acyl-homoserine lactone (AHL) signal molecules and some virulence factors, including hemolysins, proteases, extracellular nucleases production and cytotoxicity by waterborne Aeromonas hydrophila. A total of 24 strains isolated from fresh-water or diseased fish were used in the study. The majority A.hydrophila strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In another study, all clinical tested strains of A. hydrophila ( n = 20) and Aeromonas sobria ( n = 2) produced either C4-HSL and C6-HSL or both, including 10 strains that produced an additional AHL, a putative N-pentanoyl homoserine lactone (C5-HSL; Chan et al, 2011). Other studies showed similar results, e.g., A. caviae YL12 (Table 3), although additional AHLs were not systematically characterized (Bruhn et al, 2005; Morgan-Sagastume et al, 2005; Medina-Martínez et al, 2006; Schwenteit et al, 2011; Chong et al, 2012; Huang et al, 2012; Chu et al, 2013; Ochiai et al, 2013; Lim et al, 2014; Zeng et al, 2014). The HPLC data confirmed results obtained with bioassays (Table 3).…”
Section: Quorum Sensing Systems In Aeromonasmentioning
confidence: 70%
“…In another study, all clinical tested strains of A. hydrophila ( n = 20) and Aeromonas sobria ( n = 2) produced either C4-HSL and C6-HSL or both, including 10 strains that produced an additional AHL, a putative N-pentanoyl homoserine lactone (C5-HSL; Chan et al, 2011). Other studies showed similar results, e.g., A. caviae YL12 (Table 3), although additional AHLs were not systematically characterized (Bruhn et al, 2005; Morgan-Sagastume et al, 2005; Medina-Martínez et al, 2006; Schwenteit et al, 2011; Chong et al, 2012; Huang et al, 2012; Chu et al, 2013; Ochiai et al, 2013; Lim et al, 2014; Zeng et al, 2014). The HPLC data confirmed results obtained with bioassays (Table 3).…”
Section: Quorum Sensing Systems In Aeromonasmentioning
confidence: 70%
“…A set of criteria has been laid down for identifying QSI molecules: (i) a low molecular mass, (ii) highly specific, (iii) stable and resistant to hydrolytic enzymes of the host (iv) no adverse effect on the host, (v) longer side chain than the native AHLs [3234]. QSIs have been shown to be produced by plants, animals, bacteria, and other microbes [25, 26, 28, 35, 36]. The apprehension is that constant and indiscriminate usage of QSIs may put bacteria under pressure to develop means to evade this treatment procedure.…”
Section: Quorum Sensing Inhibitionmentioning
confidence: 99%
“…Continuous and indiscriminate usage of antibiotics have paved way for the development of antibiotic resistant bacteria and few which were resistant to multiple antibiotics. Antibiotics have become ineffective in controlling the virulence of bacterial pathogens [11][12][13][14][15]. Hence, novel antimicrobial agents which selectively reduce the virulence of pathogens rather than inducing antimicrobial resistance are the need of the hour [16].…”
Section: Introductionmentioning
confidence: 99%